Pemberdayaan Komunitas Perempuan dengan Pelatihan Pembuatan Produk Minuman Kesehatan Berbasis Herbal di HAPSARI, Kabupaten Deli Serdang : indonesia - Laila, Lia; Marianne, Marianne; Prasetyo, Bayu Eko; Wahyuni, Henny Sri (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Unhealthy lifestyles and the habit of consuming high-sugar drinks in the community that continues to increase lead to an increase in the occurrence of various health problems such as diabetes. The development of herbal health drinks based on natural sweeteners of stevia leaves can be an alternative solution to health drinks that are efficacious and safe for consumption, but public knowledge and awareness of this issue need to be improved. The community service team provide solutions in the form of educational activities for the community on the importance of a healthy lifestyle, the virtues of herbal-based health drinks and provide training on the process of making herbal drinks, packaging and marketing. This program was implemented in Marindal II Village, Patumbak District, Deli Serdang Regency involving the Indonesian Women's Union Association (Hapsari) community. The results of the service implementation showed that the service activities succeeded in increasing community knowledge about healthy lifestyles and herbal health drinks by 17.12%. This activity also provided skills to the participants in making herbal health drinks independently which can be developed and have economic value to  improve family welfare.